Corporate Social Responsibility and Firm Performance: Evidence from Vietnamese Listed Companies - Binh, Dao Thi Thanh; Huong, Le Thi Thanh (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study investigates the impact of socially responsible factors on corporate performance, including industries from the manufacturing and service/non-manufacturing sector. The study analyzes data of 50 Vietnamese private companies from 2015 to 2019. The analyses use five groups of stakeholders, including shareholders, employees, consumers and suppliers, environment, and general community to measure the performance of corporate social responsibilities (CSR). Meanwhile, company performance was estimated using Tobin’s Q index, return on assets, return on equity, and earnings per share. CSR activities have a positive and significant effect on the development of the companies. However, these effects are not intensive. Among CSR groups, social dimension has the most influence, while environmental aspects are the least influential. Private small- and medium-sized companies in Vietnam should focus more on social responsibility activities to enhance their brand image and benefit their stakeholders while bringing sustainable values in financial activities. This study is one of the first CSR-based research in Vietnam under the proxy of Hexun framework.